(untitled) (The Review of Diabetic Studies, 2025)
Background: Procedural sedation and analgesia (PSA) are integral to cardiac catheterisation, enabling patient comfort and procedural efficiency. In many cardiac catheterisation laboratories (CCLs), nurses administer sedation under physician supervision, a practice that has expanded internationally to address workforce demands. However, the safety, governance, and inter-professional implications of nurse-administered PSA remain debated, particularly in high-acuity settings such as Saudi tertiary hospitals. Aim: This study aimed to explore the issues and challenges associated with nurse-administered PSA in CCLs, focusing on the perspectives of nurses, cardiac catheterisation technologists, and anaesthesia technicians regarding safety, role boundaries, and institutional support. Methods: A qualitative, descriptive design was employed across three tertiary hospitals in Saudi Arabia between March and June 2025. Eighteen participants (six nurses, six technologists, and six anaesthesia technicians) were recruited using purposive sampling. Data were collected through semi-structured interviews and focus-group discussions, transcribed verbatim, and analysed thematically following Braun and Clarke’s (2019) six-step approach. Credibility and dependability were ensured through member checking, peer debriefing, and triangulation. Results: Three overarching themes emerged: (1) Clinical and safety concerns, including inadequate monitoring, inconsistent use of capnography, and divided staff attention; (2) Inter-professional role boundaries, characterised by ambiguous responsibilities between nurses, technologists, and physicians; and (3) Organisational and policy gaps, encompassing limited formal training, variable protocols, and insufficient leadership oversight. Despite these challenges, teamwork and informal collaboration were identified as key enablers of safety. Conclusion: Nurse-administered PSA in Saudi CCLs enhances efficiency but exposes systemic vulnerabilities when policies and training are inconsistent. Establishing national PSA standards, mandating competency certification, ensuring access to monitoring technologies, and strengthening interdisciplinary communication are critical for safe implementation. Findings support the development of a unified national framework through the Saudi Commission for Health Specialties to align PSA practice with international best-practice standards.